Ruptured cystic artery pseudoaneurysm after self‐expandable metal stent placement for malignant biliary obstruction - Takafumi Mie; Takashi Sasaki; Kiyoshi Matsueda; Takeshi Okamoto; Tatsuki Hirai; Takahiro Ishitsuka; Manabu Yamada; Hiroki Nakagawa; Takaaki Furukawa; Tsuyoshi Takeda; Akiyoshi Kasuga; Masato Ozaka; et al. (DEN Open)
Abstract We report a case of ruptured cystic artery pseudoaneurysm after self‐expandable metal stent placement for malignant biliary obstruction. A 78‐year‐old woman on palliative care after chemotherapy for unresectable pancreatic head cancer presented with obstructive jaundice. Imaging revealed a dilated common bile duct and an enlarged gallbladder with cystic wall thickening. Endoscopic retrograde cholangiopancreatography was performed and a fully‐covered self‐expandable metal stent was placed in the bile duct, leading to resolution of jaundice. She presented with hematochezia 7 days later. Contrast‐enhanced computed tomography revealed a cystic artery pseudoaneurysm with extravasation of contrast into a blood‐filled gallbladder. Hemostasis was achieved after emergent transcatheter arterial embolization. Rupture of cystic artery pseudoaneurysm should be raised as a differential diagnosis for hemobilia after self‐expandable metal stent placement, particularly in cases accompanied by inflamed gallbladders.